2018
DOI: 10.1039/c7dt04108j
|View full text |Cite
|
Sign up to set email alerts
|

Combining the platinum(ii) drug candidate kiteplatin with 1,10-phenanthroline analogues

Abstract: Platinum complexes of the type [Pt(P)(A)] where P is a derivative of 1,10-phenanthroline and A is cis-1,4-diaminocyclohexane (1,4-dach), have been synthesised and characterised by ultraviolet spectroscopy, elemental microanalysis, nuclear magnetic resonance and X-ray crystallography. The calf-thymus DNA binding affinity of these complexes was determined by isothermal titration calorimetry, revealing higher DNA affinity than their 1S,2S-diaminocyclohexane analogues. In vitro cytotoxicity was assessed in eleven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
0
2
0
1
Order By: Relevance
“…However, this eventuality is unlikely since it has been found 29−31 that the platinum(II)−oxalate complex with RR-DACH (1) was more active than the corresponding complexes with SS-DACH, 29−31 whereas platinum(II)−complex 5 with RR-DACH was less active than the corresponding complexes with SS-DACH. 32 An intriguing potency of the compounds based on 5 was observed for breast cancer cells MDA-MB-231 and colon carcinoma cells HCT-116 [for instance, the IC 50 values found for the investigated Pt(IV) derivatives of 5 were as low as 0.06−0.07 μM (Table 1)], that is, by approximately two orders of magnitude lower than the IC 50 values found for clinically used anticancer platinum drugs. A common feature of these cancer cells is that both carry RAS mutation that can cause the tumor to become resistant to drugs usually used to treat these types of cancer cells.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, this eventuality is unlikely since it has been found 29−31 that the platinum(II)−oxalate complex with RR-DACH (1) was more active than the corresponding complexes with SS-DACH, 29−31 whereas platinum(II)−complex 5 with RR-DACH was less active than the corresponding complexes with SS-DACH. 32 An intriguing potency of the compounds based on 5 was observed for breast cancer cells MDA-MB-231 and colon carcinoma cells HCT-116 [for instance, the IC 50 values found for the investigated Pt(IV) derivatives of 5 were as low as 0.06−0.07 μM (Table 1)], that is, by approximately two orders of magnitude lower than the IC 50 values found for clinically used anticancer platinum drugs. A common feature of these cancer cells is that both carry RAS mutation that can cause the tumor to become resistant to drugs usually used to treat these types of cancer cells.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…Thus, it is possible to speculate that the considerable differences in antiproliferative activities observed for the compounds based on 1 and 5 (Table ) might also be a consequence of different enantiomericity of their amine ligands. However, this eventuality is unlikely since it has been found that the platinum­(II)–oxalate complex with RR -DACH ( 1 ) was more active than the corresponding complexes with SS -DACH, whereas platinum­(II)–complex 5 with RR -DACH was less active than the corresponding complexes with SS -DACH …”
Section: Resultsmentioning
confidence: 99%
“…Os espectros de RMN de 1 H dos derivados de 5-alquil-1,3,4-oxadiazol-2-tiona apresentaram sinais característicos de alcanos na região entre δ 0,8-2,7 ppm, bem como a presença de um singleto largo referente ao hidrogênio NH do anel 1,3,4-oxadiazol em torno de Enquanto que no complexo 7 foram observados sinais localizados em δ 7,80; 7,98; 8,74 e 9,68 ppm que são atribuídos aos hidrogênios da fenantrolina (KOTZÉ et al, 2009;PAGES et al, 2018…”
Section: Rmn De 1 Hunclassified